The Role of Accounting in Corporate Turnaround and Restructuring Strategies (gjstudies, 2025)
This research introduces a novel computational accounting framework that reconceptualizes the role of accounting in corporate turnaround and restructuringstrategies. Moving beyond traditional financial reporting and compliance functions,we propose that accounting systems can be transformed into dynamic, predictiveengines for strategic decision-making during periods of corporate distress. Ourmethodology integrates principles from computational linguistics, network theory,and machine learning to analyze accounting data not merely as historical recordsbut as complex signals embedded within organizational communication and control systems. We develop a multi-layered analytical model that processes qualitative disclosures, quantitative financial statements, and internal control narrativesto identify early-warning indicators of distress and to simulate the outcomes ofvarious restructuring interventions. The model employs a hybrid architecture combining transformer-based natural language processing for narrative analysis withgraph neural networks to map the interdependencies between financial variablesand operational processes. Our results, derived from a proprietary dataset of 150distressed firms across multiple industries, demonstrate that this computational accounting approach can predict successful turnaround outcomes with 87% accuracy,significantly outperforming traditional ratio-based models. Furthermore, we identify previously unrecognized patterns in how accounting information flows influencemanagerial decision-making during restructuring, revealing that the semantic coherence between financial and narrative disclosures serves as a critical predictor ofrestructuring success. This research contributes original insights by reframing accounting as an active, computational participant in corporate revival rather than apassive recorder of financial events, opening new interdisciplinary pathways betweenaccounting, computer science, and strategic management.